Prenatal glucocorticoids exposure and adverse cardiovascular effects in offspring - Zhao, Chenxuan; He, Lei; Li, Lingjun; Deng, Fengying; Zhang, Meihua; Wang, Changhong; Qiu, Junlan; Gao, Qinqin (Frontiers in Endocrinology, 2024)
Glucocorticoids (GCs) are steroid hormones fundamental to the body's normal physiological functions and are pivotal in fetal growth and development. During gestation, the mother's cortisol concentration (active GCs) escalates to accommodate the requirements of fetal organ development and maturation. A natural placental GCs barrier, primarily facilitated by 11β hydroxysteroid dehydrogenase 2, exists between the mother and fetus. This enzyme transforms biologically active cortisol into biologically inactive corticosterone, thereby mitigating fetal GCs exposure. However, during pregnancy, the mother may be vulnerable to adverse factor exposures such as stress, hypoxia, caffeine, and synthetic GCs use. In these instances, maternal serum GCs levels may surge beyond the protective capacity of the placental GCs barrier.Moreover, these adverse factors could directly compromise the placental GCs barrier, resulting in excessive fetal exposure to GCs. It is well-documented that prenatal GCs exposure can detrimentally impact the offspring's cardiovascular system, particularly in relation to blood pressure, vascular function, and heart function. In this review, we succinctly delineate the alterations in GCs levels during pregnancy and the potential mechanisms driving these changes, and also analyze the possible causes of prenatal GCs exposure. Furthermore, we summarize the current advancements in understanding the adverse effects and mechanisms of prenatal GCs exposure on the offspring's cardiovascular system.